2016
DOI: 10.3389/fpsyg.2016.00504
|View full text |Cite
|
Sign up to set email alerts
|

“If It Feels Right, Do It”: Intuitive Decision Making in a Sample of High-Level Sport Coaches

Abstract: Comprehensive understanding and application of decision making is important for the professional practice and status of sports coaches. Accordingly, building on a strong work base exploring the use of professional judgment and decision making (PJDM) in sport, we report a preliminary investigation into uses of intuition by high-level coaches. Two contrasting groups of high-level coaches from adventure sports (n = 10) and rugby union (n = 8), were interviewed on their experiences of using intuitive and deliberat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…A related limitation is that the generation of coaching knowledge may be tacit (Nash & Collins, 2006) and hence coaches may not be in a position to accurately report all of the origins of their knowledge. Nonetheless, it is suggested that expert coaches require an extensive foundation of declarative knowledge before they can effectively utilise 'skilled intuition' (Abraham et al, 2006;Collins, Collins & Carson, 2016;Nash & Collins, 2006), and therefore it is particularly concerning that none of the coaches reported any explicit knowledge of specific approaches to technique refinement.…”
Section: Discussionmentioning
confidence: 99%
“…A related limitation is that the generation of coaching knowledge may be tacit (Nash & Collins, 2006) and hence coaches may not be in a position to accurately report all of the origins of their knowledge. Nonetheless, it is suggested that expert coaches require an extensive foundation of declarative knowledge before they can effectively utilise 'skilled intuition' (Abraham et al, 2006;Collins, Collins & Carson, 2016;Nash & Collins, 2006), and therefore it is particularly concerning that none of the coaches reported any explicit knowledge of specific approaches to technique refinement.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity arises in the nuances associated with the application and adaptation of the process, rather than in its' replication (cf. Collins, Collins & Carson, 2016). This raises a question of whether adventure sports coaching is or can ever be a simply procedural approach and it challenges the current employment of competency-focused training and assessment for coaches in favour of a combined process that includes a decisionand judgment-focused approach (c.f.…”
Section: Discussionmentioning
confidence: 99%
“…Coaches rely on their "gut instinct" in many aspects of coaching (Collins et al, 2016;Lyle & Cushion, 2017;Lyle & Vergeer, 2013;Roberts et al, 2019). Coaching intuition is often linked with quick reaction time (i.e.…”
Section: Intuition and Decision-making -An Ecological Perspectivementioning
confidence: 99%
“…Much of the existing research into coach decision-making labels non-deliberative coach cognitions as "intuitive" (Christensen, 2009;Collins et al, 2016;Day, 2016, Giske et al, 2013, Trottier, 2016, "instinctual" (Fiander et al, 2013;Gines, 2017, Lund & Söderström, 2011Thelwell et al, 2008), or "tacit" (Christensen, 2009;Nash & Collins, 2006) and "difficult to articulate" (Collins et al, 2016), among other terms, with little attempt to understand the experiences and knowledge used to make these intuitive yet clearly informed decisions. Nash and Collins (2006) argued that "seemingly instinctive" (p. 470) decisions made by expert coaches are a result of the dynamic and complex interaction between types of knowledge (tacit and declarative) and memories built from experience and reflection.…”
Section: Intuition and Decision-making -An Ecological Perspectivementioning
confidence: 99%